2008
DOI: 10.2139/ssrn.1331318
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and Bank Efficiency in the Asia Pacific Region

Abstract: This paper focuses on efficiency measures of banks from six countries in East Asia. We use a two-stage approach to study the post-crisis period 1999-2004. We first estimate technical efficiencies using Data Envelopment Analysis and test for cross country differences. Efficiency scores are relatively high for South Korea and relatively low for the Philippines. We then investigate the link between ownership structure and efficiency controlling for various factors such as size, risk and the economic environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…However, a few studies find that state-owned banks are more efficient (Gardener et al 2011;Wang et al 2014;Dong et al 2014;Berger et al 2009) than other types of banks and are related to higher stockholder value (Hossain et al 2013). Other studies (Barry et al 2008), however, find no significant difference between state-owned banks and privately-owned banks. Micco et al (2007) argues that state-owned banks in developing countries have higher costs and lower profits, while those in developed countries have no significant difference in costs and profits.…”
Section: State Ownership In the Banking Industrymentioning
confidence: 97%
See 1 more Smart Citation
“…However, a few studies find that state-owned banks are more efficient (Gardener et al 2011;Wang et al 2014;Dong et al 2014;Berger et al 2009) than other types of banks and are related to higher stockholder value (Hossain et al 2013). Other studies (Barry et al 2008), however, find no significant difference between state-owned banks and privately-owned banks. Micco et al (2007) argues that state-owned banks in developing countries have higher costs and lower profits, while those in developed countries have no significant difference in costs and profits.…”
Section: State Ownership In the Banking Industrymentioning
confidence: 97%
“…Empirical evidence revealed the better performance of China's four largest state-owned banks (Wang et al 2014;Dong et al 2014; Tan and Anchor 2017) over other banks in China. After estimating bank efficiency in Hong Kong, Indonesia, Korea, Malaysia, the Philippines, and Thailand, Barry et al (2008) found that state-owned banks were not significantly different from privately-owned banks.…”
Section: State Ownership In the Banking Industrymentioning
confidence: 98%
“…Our sample is consisting of 20 domestic commercial banks (4 state-owned banks and 16 private-owned banks) during the period from 2004 to 2009, totaling 120 observations. Berger & Mester (1997) concur with De Young (1997) that a six-year period reasonably adequate of not considered as too short or too long period (in Barry et al, 2008) Berger & Humphrey (1997) commented on the difficulty of variable selection in performance of banks using DEA since there is no perfect approach on the explicit definition and measurement of banks" input and outputs. The primary approaches in measureing banks" input and outputs are the production approach and intermediation approach (Barr, 2002;Galagedera & Edirisuriya, 2004;Hermes & Vu, 2008;Saad & Mousawi, 2009).…”
Section: Data and Variablesmentioning
confidence: 99%
“…There are many literary works that combine the use of DEA and Tobit Regression (e.g. Barry et al 2010;Berger and Humphrey, 1990;Wang et al 2006;Pande and Patel, 2013). In the real estate industry, Anderson et al(1998) use DEA and Tobit Regression to measure the efficiency levels of residential real estate brokerage firms.…”
Section: Tobit Regression Modelmentioning
confidence: 99%